A spatial and temporal assessment of microplastics in seafloor sediments: A case study for the UK - Bakir, Adil; Doran, Denise; Silburn, Briony; Russell, Josie; Archer-Rand, Simeon; Barry, Jon; Maes, Thomas; Limpenny, Caroline; Mason, Claire; Barber, Jon; Nicolaus, E.E. Manuel (Frontiers in Marine Science, 2023)
Seafloor sediments have been defined as sinks for microplastics in the marine environment and could therefore represent suitable matrices for their long-term monitoring. On a regional aspect, the adoption of a common indicator for microplastics in seafloor sediments would allow regional monitoring and assessments through international frameworks such as OSPAR. This study presents the findings of a research and development project monitoring the occurrence and abundance of microplastics in UK seafloor sediments for the period 2013-2021, supporting the development of a national monitoring programme for microplastics in seafloor sediments for the UK (England and Wales). A fast-screening technique based on Nile Red staining of polymers coupled with µ-FTIR was applied and validated using µ-FTIR-FPA. Microplastic particles were detected in all 189 sediment samples from 15 stations selected around the UK for each investigated year (2013 - 2021). Microplastic concentrations (20 – 5000 µm) ranged from 133 – 6,933 particles kg-1 dry weight sediment for 2020-2021. Microplastics mainly consisted of fragments (73%), fibres (19%) and spheres (8%). Plastic fragments ranged from 46 to 3276 µm and plastic fibres from 300 to 1731 µm in length with a mean diameter of 16 µm. Single particle analysis using µ-FTIR indicated a prevalence of Rayon, PP, Rayon/Nylon/Polyester blends, Rubber, PS, PE, PA, PVC, Acrylic, EMAA and PET. Fragments were mainly white in colour (46%) followed by brown (38%), black (1%), blue (1%) and orange (1%). Fibres were mainly white in colour (57%) followed by black (14%), orange (14%) and red (14%). A trend assessment at the UK regional seas levels indicated little visual evidence of any trends in the abundance of microplastics over time in any of the regional seas – with the possible exception of the Northern North Sea with a reduction in abundance over time for the time-period 2013-2021.